BASIC COMPETENCE ELEMENTS ANALYSIS OF 7 TH GRADE TEXTBOOK “WHEN ENGLISH RINGS THE BELL” - Rahadyan, Fakhri Muhammad; Rozy, Fery Fahrur; Nopriyanti, Irnella (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2024)
In education, textbooks are a source of material that is very much needed by students, for that in designing textbooks, especially in terms of basic competencies, it must be considered. Whether the existing material meets the standards or the material presented includes all the basic skills. The research aimed to analyze the basic competence elements in "When English Ring the Bell" 7-grade book based on curriculum 2013. It is a set of plans and arrangements regarding the objectives, content, learning materials, and methods used as guidelines for implementing learning activities to achieve a specific education. The research focuses on explaining the relevance of English textbooks with 2013 English curriculum material based on one of the experts and from the National Education Standard Agency using descriptive qualitative method. With this research, we will find out that the 7th grade English book already includes the basic elements of competence by the given standards, so it is proper to be used in learning activities.